The Leadership Role of Madrasah Heads on Teacher Teaching Motivation at MTs NW Karang Baru, East Lombok Regency - Harun, Muh Alawi (al-Hikmah : Jurnal Studi Islam, 2021)
The head of the Madrasah must prioritize duties, responsibilities and foster a harmonious relationship between subordinates and superiors. Indeed, the Head of Madrasah is responsible for directing the vision and resources to a department that Increases Teacher Work Motivation through the Leadership Role of the Head of Madrasah can produce other things effectively and efficiently. In this case the head of the madrasa must be responsible for the work of others, be responsible for the results achieved, strictly speaking, the leader must be responsible for the development and sustainability of the madrasa he leads. This study aims to determine the leadership role of madrasah principals on teacher work motivation to review what efforts are made by madrasah principals in order to achieve an increase in teacher performance motivation in MTs NW Karang Baru, East Lombok Regency. This research is descriptive qualitative, with data collection techniques observation, documentation and interviews. Researchers used data reduction, data display and conclusion drawing as data analysis methods, then researched using data triangulation methods as a method to check the validity of the data obtained in order to obtain valid data. The results of this study are First, the Leadership Role of Madrasah/School principals in teacher development to increase teacher motivation carried out by the head of MTs NW Karang Baru, Wanasaba District, which focuses on two types of coaching, namely: First, discipline development by: giving direction, being an example, and forming a special team in the field of teacher discipline. Second, fostering teacher professionalism, namely by: holding and ordering teachers to attend seminars and training, collaborating with other educational institutions, bringing in experts, providing opportunities for teachers to continue their education, placing teachers in the right proportions, evaluating teacher work. , provide opportunities for teachers to supervise each other, provide and optimize educational facilities and equipment. Second, the principal’s leadership efforts in improving teacher performance are focused on increasing internal and external motivation. Increasing internal motivation by: creating a harmonious situation and cooperation between teachers, involving teachers in every school activity, giving teachers the right to express opinions for school developments, trying to fulfill the wishes of teachers and completing all the needs needed in carrying out his job. Second, increasing external motivation by: giving rewards.